Machiavellian personality and its relationship to the attitudes towards academic cheating among university students - Elballah, Khaled Awad; Aljarboa, Nada Ali (International Journal of Innovative Research and Scientific Studies, 2025)
The current study aimed to investigate the nature of the relationship between the dimensions of Machiavellian personality and attitudes towards academic cheating among university students. The sample consisted of 324 male and female students from scientific and humanities colleges at King Faisal University. The Machiavellianism scale, prepared by Dahling et al. [1], and the Attitudes toward Academic Cheating Scale (ATC) developed by [2] were applied. The results of the study showed a positive correlation between the dimensions of Machiavellianism and positive attitudes towards academic cheating. There was also a negative correlation between the dimensions of Machiavellian personality and negative attitudes towards academic cheating. The results of the study also showed statistically significant differences in favor of males in the dimensions of Machiavellian personality, and differences between students of scientific and humanities colleges in positive attitudes towards academic cheating in favor of humanities colleges.